A high-payload, reversible data hiding scheme based on histogram modification in JPEG bitstream. (2nd October 2016) - Liu, X.-L.; Chang, C.-C.; Lin, C.-C.; Yuan, S.-M.
Abstract : In this paper, we have presented a high-payload, reversible data hiding scheme that is focused on embedding secret data into joint photographic experts group (JPEG) bitstream by using histogram modification. In JPEG, for AC coefficients, 162 different variable length codes (VLCs) are defined and assigned by Huffman coding for all 162 run/size possibilities. After parsing VLC usage in the bitstream, we generated a histogram of run/size . According to a peak point and the nearest zero point of the histogram, the secret data were embedded by modifying the corresponding VLC values slightly. The experimental results and comparing the performance of our scheme with those of other existing schemes demonstrated that the proposed scheme preserved the quality of the image with no distortion and achieved the goal of high embedding capacity.